A real asset management approach for Islamic investment in containerships. Issue 1 (6th January 2020) - Abdullah, Adam; Hassan, Rusni; Kassim, Salina
Abstract : Purpose: The purpose of this paper is to provide a real asset management investment appraisal of the performance of containerships as a primary segment within international shipping, to facilitate Islamic equity investment through a shipping fund. The objectives are to evaluate the risks and returns of shipping under the framework of Islamic equity finance, and to analyze the performance of investing in containerships over the long term, to appeal to retail and institutional clients of Malaysian asset management institutions. Design/methodology/approach: Accordingly, the methodology adopts an investment analysis of a full population of historical data over a period of 20 years, to evaluate performance involving a maritime return on investment (MROI), internal rate of return (IRR), net yield and standard deviation measures of risk and return. Findings: The findings reveal that while earnings are volatile in comparison to capital market expectations, unlevered, tax-free returns on containership investments outperform financial and other real assets. Research limitations/implications: Shipping is a strong growth industry with about 84 per cent of global trade carried out by the international shipping industry. The problem is that many Islamic asset management institutions and investors have essentially no exposure to Islamic investment in international shipping. Practical implications: However, shipping is a highly capital-intensive industry, and currently 75 per cent of ship lending has been conducted by European banks and financed on a conventional basis. Post-financial crisis, ship owners, ship lenders and shipyards have all been exposed to the impact of over-levered balance sheets and debt finance. There is a demand for alternative sources of finance. Social implications: By communicating risk and reward more effectively, retail and institutional investors, as well as Islamic finance institutions, will realize that the social benefit of equity finance on the basis of profit sharing is more efficient at allocating investible resources than debt finance at interest, thereby increasing investment and economic growth. Originality/value: The significance is that Islamic equity finance, rather than debt at the time-value of money, should enhance the development of international shipping.